2022
DOI: 10.1186/s12873-022-00716-3
|View full text |Cite
|
Sign up to set email alerts
|

Case management intervention of high users of the emergency department of a Portuguese hospital: a before-after design analysis

Abstract: Background Emergency department (ED) High users (HU), defined as having more than ten visits to the ED per year, are a small group of patients that use a significant proportion of ED resources. The High Users Resolution Group (GRHU) identifies and provides care to HU to improve their health conditions and reduce the frequency of ED visits by delivering patient-centered case management integrated care. The main objective of this study was to measure the impact of the GRHU intervention in reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…There were no qualitative studies identified. Thirty-five (35) were from the US [ 14 , 16 , 26 58 ], five were from Canada [ 59 63 ], three were from each of the UK [ 64 – 66 ] and Australia [ 67 69 ], two were from each of Sweden [ 15 , 70 ], Taiwan [ 71 , 72 ], and Spain [ 73 , 74 ], and one was from each of Belgium [ 75 ], Denmark [ 76 ], Portugal [ 77 ], the Netherlands [ 18 ], Singapore [ 78 ], and Switzerland [ 79 ], Fig. 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were no qualitative studies identified. Thirty-five (35) were from the US [ 14 , 16 , 26 58 ], five were from Canada [ 59 63 ], three were from each of the UK [ 64 – 66 ] and Australia [ 67 69 ], two were from each of Sweden [ 15 , 70 ], Taiwan [ 71 , 72 ], and Spain [ 73 , 74 ], and one was from each of Belgium [ 75 ], Denmark [ 76 ], Portugal [ 77 ], the Netherlands [ 18 ], Singapore [ 78 ], and Switzerland [ 79 ], Fig. 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Study population size varied widely, ranging from seven participants to over 100,000. Fifteen studies had a study population of less than 100 [ 14 , 26 , 30 , 34 , 36 , 41 , 44 , 47 , 51 , 57 , 62 , 65 , 66 , 68 , 71 ], 24 had a study population of 100–500 [ 15 , 16 , 27 , 28 , 32 , 33 , 38 , 40 , 42 , 43 , 48 50 , 53 , 55 , 58 61 , 63 , 67 , 72 , 77 , 79 ], six had a study population of 500–1,000 [ 31 , 45 , 64 , 74 , 78 , 80 ], and 13 had a study population of more than 1,000 [ 18 , 29 , 36 , 37 , 39 , 46 , 52 , 54 , 56 , 69 , 70 , 75 , 76 ], Fig. 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the importance of reducing ED waiting times and more hospital beds for mental health patients, we strongly advocate for more resources to be allocated to community mental health services with multiple benefits. On a community level, case-based management and a patient-centred approach can be tailored to specific patients’ needs, with a higher rate of patient satisfaction, better clinical outcomes, and reduced ED visits and admissions [ 82 , 83 ]. Nursing models such as the Buurtzorg [ 84 ] could be expanded to provide mental health support and social welfare services at a local level.…”
Section: Discussionmentioning
confidence: 99%